Pragmatic thinking and learning : refactor your "wetware" - Hunt, Andrew, 1964- (Pragmatic programmers., 2008)
Helps you learn how to: use the Dreyfus Model of Skill Acquisition; leverage the architecture of the brain to strengthen different thinking modes; avoid common 'known bugs' in your mind; and, manage knowledge efficiently.